М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
kennysussus
kennysussus
23.04.2020 18:44 •  Алгебра

Решите уравнение: 12+4(х-3)-2х=(5-3х)+9

👇
Ответ:
sofiacat06
sofiacat06
23.04.2020
12 + 4x - 12 - 2x = 5 - 3x + 9
12 + 4x - 12 - 2x - 5 + 3x - 9 = 0
5x = 14
x = \frac{14}{5}
x = 2,8
4,6(37 оценок)
Ответ:
krasota33
krasota33
23.04.2020
12+4х-12-2х=5-3х+9
5х=14
х=5/14
4,7(11 оценок)
Открыть все ответы
Ответ:
plesovskih
plesovskih
23.04.2020
А) x2-7x=0                         б) 3x2=0                         в) x2-12=0     x(x-7)=0                             x2=0                               x2=12 x=0   ; x-7=0                           x=0                                 x=\sqrt{12} ; x=-\sqrt{12}            x=7                             ответ: x=0                 ответ: x=  \sqrt{12}; \sqrt{12}  ответ: x=0; x=7    
4,6(30 оценок)
Ответ:
Lizasuper2003
Lizasuper2003
23.04.2020
Х^6-12x^4+48x²-16-48=0 x^6-12x^4+48x²-64=0 (x^6-64)-12x²(x²-4)=0 (x²)³-(4)³-12x²(x²-4)=0 (x²-4)(x^4+4x²+16)-12x²(x²-4)=0 (x²-4)(x^4+4x²+16-12x²)=0 (x²-4)(x^4-8x²+16)=0 (x²-4)(x²-4)²=0           (x²-4)³=0   ⇒   x²-4=0       (x-2)(x+2)=0                                                                               x-2=0     x=2                                                                           x+2=0     x=-2                           ответ:     х1=2       х2=-2
4,6(18 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ